2017
DOI: 10.2147/bctt.s130090
|View full text |Cite
|
Sign up to set email alerts
|

An effective deep-inspiration breath-hold radiotherapy technique for left-breast cancer: impact of post-mastectomy treatment, nodal coverage, and dose schedule on organs at risk

Abstract: BackgroundWe developed, applied, and prospectively evaluated a novel deep-inspiration breath-hold (DIBH) screening and delivery technique to optimize cardiac sparing in left-breast radiotherapy (RT) at our clinic. The impact of set-up and dose variables upon organs at risk (OAR) dose in DIBH RT was investigated.Methods and materialsAll patients with left-breast cancer referred between 2011 and 2014 – of all disease stages, set-up variations, and dose prescriptions – were included. Radiographers used simple scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 34 publications
1
25
1
Order By: Relevance
“…The results of the present study demonstrated the ability of DIBH in the reduction of the heart dose in patients with left-sided breast cancer as reported in previous studies [7][8][9][10][11][12]. However, similar to some reports, the collected data of the present study did not show the protective effect of this technique on the left lung [8,[15][16][17][18][19][20]. In the present study, the average of the heart D mean and Values are presented as mean ± standard deviation.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The results of the present study demonstrated the ability of DIBH in the reduction of the heart dose in patients with left-sided breast cancer as reported in previous studies [7][8][9][10][11][12]. However, similar to some reports, the collected data of the present study did not show the protective effect of this technique on the left lung [8,[15][16][17][18][19][20]. In the present study, the average of the heart D mean and Values are presented as mean ± standard deviation.…”
Section: Discussionsupporting
confidence: 87%
“…Although this technique reduces the heart dose [7][8][9][10][11][12], it seems that there are challenges in the reduction of lung dose with DIBH [13]. Despite the results of many studies showing the reduction of the ipsilateral lung dose [2,7,11,14], there are reports of no significant difference and even increasing the left lung dosimetric parameters using DIBH [8,[15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Patients who received RT in deep inspiration breath hold (DIBH) were excluded from the present analysis. [14,15] The study was approved by the local ethics committee of the University Hospital, LMU Munich (No. 352-16 ex 09/2016) and registered at German Clinical Trials Register (DRKS-ID: DRKS00011407).…”
Section: Methodsmentioning
confidence: 99%
“…There has been quite some interest on reducing the dose to the left anterior descending coronary artery (LADCA) since reports have indicated an association between LADCA irradiation and the risk of ischemic heart disease [13][14][15]. In order to optimize target coverage while maintaining a low dose to OAR, techniques for RT with respiratory gating (RG), like enhanced inspiration gating and deep-inspiration breath hold (DIBH), have successfully been implemented in RT centres during the last decade [16][17][18][19]. These techniques exploit that during a deep inspiration the heart shifts in caudal and dorsal direction compared to the breast, moving the heart away from the high dose region of typical tangential fields.…”
Section: Introductionmentioning
confidence: 99%